2022
DOI: 10.3390/geosciences12090330
|View full text |Cite
|
Sign up to set email alerts
|

The Geosites of the Sacred Rock of Acropolis (UNESCO World Heritage, Athens, Greece): Cultural and Geological Heritage Integrated

Abstract: Athens, the capital of Greece, is notable for its distinctive environment. Numerous archaeological and historical monuments contribute to the city’s cultural wealth. These cultural monuments should include geological monuments, which are part of Athens’ natural heritage. The Acropolis of Athens is one of the world’s most recognizable and admired monuments, renowned for its archaeological, historical, and touristic significance. The Acropolis Rock is also a spectacular geological heritage monument. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Rocks, fossils and other geological elements reveal the palaeogeography of the broader Greek territory, which is today reflected in a complex geomorphological environment shaped mainly by active tectonics, but also exogenous processes. Mountains, mountain ranges, island complexes, lakes, rivers, caves, beaches consist some of the rich geomorphological features extending up to almost 3,000 m of elevation and contributing to the geodiversity of the country (Drinia et al 2022).…”
Section: Study Areamentioning
confidence: 99%
“…Rocks, fossils and other geological elements reveal the palaeogeography of the broader Greek territory, which is today reflected in a complex geomorphological environment shaped mainly by active tectonics, but also exogenous processes. Mountains, mountain ranges, island complexes, lakes, rivers, caves, beaches consist some of the rich geomorphological features extending up to almost 3,000 m of elevation and contributing to the geodiversity of the country (Drinia et al 2022).…”
Section: Study Areamentioning
confidence: 99%
“…Ved 3 Ease of understanding information panels at the geosite This method emphasized the geoheritage value and geotourism potential of geological areas, contributing to its widespread use and recognition. It has been applied to promote urban geotourism and highlight geoheritage of cities like Segovia in Spain [41] and Athens in Greece [42]. Overall, the method is well-established and effective for promoting urban geotourism and highlighting the geological features and monuments present in urban areas.…”
Section: Ved 2 Representativenessmentioning
confidence: 99%
“…With the values of geoethics, the integration between geodiversity and cultural resources is able to develop the needed sense of responsibility for preserving geoheritage, not only for the enjoyability of the present communities but also for assuring its existence for the future generations [15,22]. Greece denotes an exceptional example of a geotope ensemble with solid geotouristic potential [2,7,8,[23][24][25][26]. In particular [6,7], after evaluating more than 500 geotopes of the Hellenic territory, concluded that Greece holds high geotouristic perspectives that can further support the vital tourism sector and the regional development of the Greek economy via the management of the geotopes as attractive local tourism products.…”
Section: Introductionmentioning
confidence: 99%